Accuracy of Burial Qibla Orientation in Gowa’s Allata Tradition: An Islamic Astronomy Perspective - Alamsyah Alamsyah; Ferdinan Ferdinan; Sulaeman Sulaeman; Hisbullah Salam; Mualimin Mochammad Sahid (IAIN Manado, 2026)
Determining the Qibla direction for Muslim burials is both a legal and astronomical concern. Yet some indigenous Makassar communities in Gowa Regency, South Sulawesi, continue to rely on Allata, a local tradition for orienting graves through inherited knowledge, prayer, and intuition rather than calibrated instruments. This study examines the accuracy of Allata from an Islamic astronomy perspective using an ethnographic approach and field-based Qibla measurements with Istiwa’aini and a Suunto compass. The findings show deviations of 17°–23° from the required Qibla azimuth of 292°, indicating a substantial gap between customary orientation and astronomical calculation. These deviations matter because burial orientation is not merely a spatial arrangement; it also concerns the religious propriety of placing the deceased toward the Ka‘bah, particularly within the Shafi‘i legal tradition. The findings suggest that Allata should be preserved as a living cultural practice, but its application requires astronomical verification. Structured training for Parewa, simple measurement tools, verified cemetery markers, and collaboration with ‘ilm al-falak experts are needed to improve Qibla accuracy without weakening the cultural authority of the tradition.